The Influence of Acculturation Stress on the Adjustment Process of New Female Students in Islamic Religious Education - Dini Zakia Zahra; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The acculturation process is a crucial part of the life of new female santri who enter the pesantren environment. They must adjust to various cultures, norms, and values that are different from those they bring from home. Acculturation stress often arises due to these differences, which can affect their ability to adapt to the new environment. This study aims to analyze the effect of acculturation stress on the self-adjustment process of new female santri in Islamic religious education. The method used in this research is a quantitative approach with a survey, which involves a number of new female santri from several pesantren as samples. The results showed that the level of acculturation stress experienced by santri was quite high and had a significant influence on their self-adjustment process. A good adjustment process is proven to improve the mental well-being and academic success of santri. Therefore, it is important to provide appropriate support to manage acculturation stress, so that students can adapt better. This study recommends the need for assistance programs that can help santri in overcoming acculturation stress and facilitate their adaptation process in pesantren. Thus, the mental well-being and academic achievement of santri will be better ensured.